ORGANIC AND/OR AGRO-ECOLOGICAL FOODS IN SCHOOL MEALS IN MUNICIPALITIES IN RIO GRANDE DO SUL, BRAZIL - Letiane de Souza Machado; Fernanda Camboim Rockett; Gabriela Cheuiche Pires; Rafaela da Silveira Corrêa; Ana Beatriz Almeida de Oliveira (Universidade do Estado do Rio de Janeiro, 2018)
Objective: To describe the purchase of organic and/or agro-ecological foods for Brazil's National School Meal Program in municipalities of the state of Rio Grande do Sul, Brazil. Method: A cross-sectional study, in which 497 municipalities in Rio Grande do Sul were sent an online questionnaire whose questions covered the following issues: whether organic and/or agro-ecological foods were purchased in 2014, major barriers to purchasing, factors that influenced the choice of foods, certification, and the foods purchased. Results: Responses were received from 362 municipalities, and 94 of them (26.0%) reported that they purchase organic and/or agro-ecological products,which accounts for 18.9% of the total number of municipalities in Rio Grande do Sul. The main barriers to the purchase of these foods were low amount (54.4%; n=197) and low variety (51.9%; n=188); in general, the main motivations were concerns about the health and the environment, as reported by more than 60% of municipalities. Of these, 60.6% (n=57) reported that the products had no certification or their certification was unknown. The products most commonly purchased were: lettuce, orange and cabbage. Conclusion: Although at low percentages, organic and/or agro-ecological foods are being included in school meals in the state of Rio Grande do Sul. Further integration is needed among subject-matter experts, family farmers and other stakeholders in order for this practice to be developed and become effective. DOI:10.12957/demetra.2018.30699